EXPRESSION OF OXIDATIVE STRESS AND INFLAMMATORY INDICATORS FOR CORONARY ARTERY DISEASE IN KAWASAKI DISEASE - Haibo Zhang (Mediterranean Journal of Hematology and Infectious Diseases)
Background: The paper was to investigate the clinical relevance of oxidative stress (OS) and inflammation-associated target in coronary artery lesions (CALs) associated with Kawasaki disease (KD).